A Clinical-Psychological Perspective on Somatization Among Immigrants: A Systematic Review - Lanzara, Roberta; Scipioni, Mattia; Conti, Chiara (Frontiers in Psychology, 2019)
BACKGROUND: Somatization is defined as the tendency to experience and communicate psychological concerns in the form of physical symptoms and to seek medical help for them. Somatic and psychopathological conditions (anxiety, depression, post-traumatic stress disorder and somatization) are frequent among immigrants belonging to various ethnic groups. We carried out a systematic review analyzing the relationship between migration and somatization by providing a qualitative data synthesis of the studies. METHODS: We conducted, according to PRISMA guidelines, a systematic search of the literature on PubMed, Scopus, ISI Web of Science, PsycINFO, Google Scholar and ScienceDirect. Search terms were “immigrant* OR migrant* OR immigration OR migration” AND “somatization”. RESULTS: The initial search identified 298 records, of which 43 research reports met the predefined inclusion criteria and were analyzed. Most studies (n = 40, 93%) were cross-sectional. Somatization was found to be prevalent and significant in individuals with migratory background, especially when it is related to traumatic events, post-traumatic symptoms and post-migration living difficulties. Furthermore, some studies suggested that the tendency to report physical symptom complaints could be an expression of psychological distress in immigrants. The tendency to somatize emotional distress was associated with poor mental health, low quality of life and help-seeking behaviors in migrant populations. CONCLUSION: Health care professionals should be aware of the tendency to somatize the traumatic experience in immigrant patients; thus, patients with these characteristics need special attention. In this regard, clinical management should include efforts to manage emotional distress, with special attention to social, cultural, and linguistic differences.